Recent Remote Sensing Sensor Applications (IntechOpen, 2023)
This book provides a comprehensive overview of remote sensing and its various applications. In remote sensing applications, various sensors that begin as both active and passive sensors are used. Active remote sensing transmits electromagnetic radiation that is both emitted and reflected, in contrast to passive remote sensing, which merely measures electromagnetic radiation that is reflected from the target. This book includes nine chapters that examine remote sensing for detecting ice, tracking and monitoring deforestation, identifying crop regions infected with disease, mineral and geological mapping, and much more.